Aesthetic Imaginaries of Children in the Architecture of Play Spaces: The Wendy House as a Case Study - Genís Vinyals, Mariona; Miralles Jori, Roger; Valero Macip, Júlia; Planelles Salvans, Jordi (Historia y Memoria de la Educación, 2025)
This article examines the influence of architecture on the formation of children's aesthetic imagery, using the Wendy House as a case study. Its aim is to analyze how the design of these playhouses, particularly in the first half of the 20th century, contributed to children's aesthetic experience. It focuses on three key indicators: the connection between the playhouse and its environment, the child-sized scale of the space, and the aesthetic richness of materials and symbolism. The methodology consisted of a systematic review of historical records and archives, analysing five representative examples of playhouses in the United States, the United Kingdom, and Spain, selecting those that retained their original characteristics. An in-depth study was conducted on a mid-20th century playhouse in Barcelona, exploring its resignification and restoration in a contemporary context. The results demonstrate the importance of these three indicators in generating a significant aesthetic experience. The relevance of the connection between the playhouse and its surroundings was evidenced, whether in a carefully designed garden or a natural space that evokes specific imagery. The child-sized scale, adapted to children's dimensions and needs, was essential for playful immersion. Furthermore, the aesthetic richness of the materials and symbolic ornamentation greatly enhances the experience. The study concludes that these factors are essential in creating children's aesthetic imagery and advocates for the conservation of existing playhouses, recommending the application of their design principles in contemporary projects to foster imagination and children's aesthetic development.Principio del formulario